ChemInform Abstract: Regio‐ and Stereoselective Synthesis of Ensulfonamides/Enamides via Catalyst‐Free Intermolecular Addition of Indoles/Pyrroles/Imidazole to Allenamides. Issue 8 (February 2016) - Li, Honghe; Ma, Ting; Li, Xiaoxiao; Zhao, Zhigang
Abstract: Enamides are obtained using acyl instead of tosyl as amino‐protecting group of the allenamides.